The Influence of Product Quality, Brand Image and Promotion on Purchase Decisions for Hori LED Lights in Bogor City - Putri, Aisyah Astri; Andari, Titiek Tjahja; Samsuri (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This study aims to determine the effect of product quality, brand image and promotion on purchasing decisions for Hori LED lamps in the city of Bogor. The population in this study were consumers of Hori LED lamps, with a sampling technique using the method Proportional sampling so that 100 respondents were obtained using data analysis, namely multiple linear regression analysis. The results of the study indicate that simultaneously the quality of the product, brand image and promotion have a positive and significant effect on purchasing decisions, partially indicating that all independent variables of product quality, brand image and promotion have a positive and significant effect on purchasing decisions